The influence of marketing abilities, innovation abilities and learning abilities on the performance of UKM in The Region Diy Province - Muhlisin, Muhammad; Rahman, Moh. Abd. (Technium Social Sciences Journal, 2021)
Small and Medium Enterprises (UKM) in various countries have proven to be the backbone of the economy, UKM are the largest group of economic players in Indonesia and have proven to be the key to securing the national economy during times of economic crisis as well as being the dynamics of post-crisis economic growth. The existence of small industries is a fact of a very large entrepreneurial spirit among the people that is able to support the national economy. The purpose of this study was to examine the effect of marketing ability on the performance of UKM in Yogyakarta Province. To test the influence of innovation ability on the performance of UKM in DIY Province, To test the effect of learning ability on the performance of UKM in the Province of DIY, To test the effect of marketing ability, innovation ability and learning ability simultaneously on the performance of UKM in Yogyakarta Province. The results of this study can be an input for UKM to survive in the fierce competition, especially in the long term for products offered by other competitors. Second, the results of this study can be an input for UKM, especially UKM affected by the Covid-19 pandemic, to pay attention to the products produced, for example in the form of applying the concept of innovation and creativity of products produced in both form and packaging. Third, the results of this study can be used as input for UKM to create learning patterns of production needs for technology. Fourth, the results of this study can be an input for UKM implementing innovation in their business activities will be able to encourage efforts to increase UKM business development. Furthermore, business development can boost the marketing capabilities of UKM, meaning that businesses continue to develop in line with the learning abilities and performance of UKM. Statistical analysis using the Statistical Product and Service Solutions (SPSS) program. keyword : marketing abilities, innovation abilities, learning abilities, performance of ukm.